Implementasi Gerakan Ayo Kuliah Melalui Program Keluarga Harapan di Provinsi Lampung - Mubarak, Abdul Mahdi Fauzan; Juwita, Masayu Nila (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
The efforts of the Lampung provincial government through the Social Service to break the chain of poverty are by increasing the educational level of children from KPM (Beneficiary Families) PKH, namely through various social programs and driven by the innovation of the Let's Go to College (GAK) Movement which is currently running. (GAK) is complementary social assistance as well as a complement to PKH social assistance to families and/or individuals who are poor, underprivileged, and/or vulnerable to social risks in the form of services in the education sector through a series of systematic activities. (GAK General Guidelines). This research aims to analyze and describe the implementation of GAK through PKH and the aspects that influence it. The research uses a descriptive qualitative approach, where researchers go directly to the field to obtain accurate data. The sources and types of data used are primary data and secondary data. Data collection techniques include interviews, observation, documentation and literature/library studies. Data analysis was carried out by means of data reduction, data presentation and drawing conclusions. GAK provides results and impacts in accordance with its goal, namely increasing the level of KPM PKH children in Lampung province.